2009
DOI: 10.1002/hed.21004
|View full text |Cite
|
Sign up to set email alerts
|

Role of chest CT in staging of oropharyngeal cancer: A systematic review

Abstract: Background. The prevalence of synchronous or metastatic tumors in patients with head and neck squamous cell carcinoma (HNSCC) ranges from 6% to 20% and has implications for prognosis and management of the primary disease. There is no consensus about the role of chest CT prior to definitive treatment patients with HNSCC.Methods. A systematic review of all chest CT studies in relation to HNSCC was performed, together with a review of our local database.Results. Twenty-four studies were identified in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
10
0
2
Order By: Relevance
“…Those patients with recurrent head and neck cancers were more likely to have malignant changes on chest CT, either metastasis or primary lung cancers. This supported previous evidence that those patients with recurrent head and neck cancers are more likely to have malignant involvement of the lungs …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Those patients with recurrent head and neck cancers were more likely to have malignant changes on chest CT, either metastasis or primary lung cancers. This supported previous evidence that those patients with recurrent head and neck cancers are more likely to have malignant involvement of the lungs …”
Section: Discussionsupporting
confidence: 90%
“…This supported previous evidence that those patients with recurrent head and neck cancers are more likely to have malignant involvement of the lungs. 24 In 2013, Alford et al 25 reported on patients with higher grade primary head and neck cancers, with initially indeterminate lung nodules who were more likely to have lung metastases. In 2014, Fukuhara et al 26 investigated lung nodules in 332 patients with head and neck cancer and demonstrated that having pulmonary nodules on an initial CT scan increased the risk of developing lung metastases.…”
mentioning
confidence: 99%
“…The sensitivity of chest x-ray is one half that of CT scanning. 8 At present, the detection of lower airway tumors can be assumed to have been improved with routine use of sensitive CT scanning of the thorax.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of synchronous lung tumors or thoracic metastases in patients with head and neck cancer have prognostic implications and may have major impact on treatment 4,8 . In addition, second primary tumors account for approximately half of deaths in patients with successfully eradicated primary head and neck cancer 9 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…The PET/CT has been highlighted as effective in detecting chest metastases or synchronous primary lung tumors, but at the moment, it still has a higher cost than CT, is not as widespread, and some studies do not show diagnostic superiority both in early cases and in newly diagnosed ones as for the possible doubts, like the uncharacteristic micronodules 8,11 . The dramatic change in technology in recent years also enhances the use of CT, the advent of multi-slice CT in the 1990s enabling shorter examination time, closer proximity in cuts and higher detailing of dimensions and objects' characteristics 7 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%